Resilient Personality Pada Remaja Yang Mengalami Konflik Keluarga - Salmiati; Sri Nurhayati Selian (Jurnal Ilmu Bimbingan dan Konseling, 2026)
This research aims to describe resilient personality in adolescents experiencing family conflicts. The method used in this study is a qualitative approach with in-depth interview techniques on three adolescent respondents with different family conflict backgrounds. The research results show that the family conflicts experienced by the respondents include parental arguments, divorce, economic problems, and relationships with stepparents. These conflicts have psychological impacts such as feelings of anger, sadness, fear, difficulties in emotion regulation, and barriers in social relationships. Nevertheless, all respondents demonstrated the ability to endure and adapt through various coping strategies, such as avoiding conflicts, seeking social support, and calming themselves. Furthermore, this study found that each respondent has a different form of resilient personality, namely independence and self-confidence, future orientation, as well as emotion regulation skills and social responsibility. These findings indicate that family conflicts not only have negative impacts but can also serve as factors in shaping adolescents' psychological strengths. Therefore, it is important to understand the role of resilience in helping adolescents face family conflicts adaptively.